SINTESIS SENYAWA 4’-HIDROKSI-4-METOKSIKALKON DAN UJI AKTIVITAS ANTIBAKTERI TERHADAP BAKTERI KONTAMINAN PRODUK DARAH - Wiwit Sepvianti; Serafica Btari Christiyani Kusumaningrum (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Despite of the blood products are crucial for health, it cannot be separated from the risks of bacterial contamination. The bacterial contamination obtained from collecting and processing blood processing. Various species of positive and negative Gram bacteria are known to be bacterial contaminants in blood products such as thrombocyte concentrate, packed red cell, dan whole blood. Therefore, it is essential to find an antibacterial compound that could inhibited the growth of bacterial contaminant in blood products. Chalcone compounds are known to become one of antibacterial since they have an unsaturated-ketone-group which acts as an antibacterial because it can damage the bacterial cell wall. The presence of hydroxyl group has important role for inhibiting bacterial contaminant growth as well. In this research, 4’-hydroxy-4-methoxychalcone was synthesized through the Claisen-Schmidt condensation reaction. The characterization of the chalcone compounds was carried out by mass spectroscopy using gas chromatography-mass spectroscopy (GC-MS) and identification of functional groups using Fourier transform infrared (FTIR). Bacterial contaminants from blood products that were used: Acinetobacter, Escherichia coli, Bacillus sp, and Staphylococcus aureus. In addition, Staphylococcus aureus from the American Type Culture Collection (ATCC) was used as comparing isolates. The antibacterial activity was analyzed by inhibition area method. The results showed that 4’-hydroxy-4-methoxychalcone successfully synthesized with the reaction product in yellow crystal formation with yield of 72,80%, relative purity 100%, and m/z 254. Antibacterial activity of chalcone compounds at various concentrations of 6.25 ppm; 12.5 ppm and 25 ppm against Gram-positive and Gram-negative bacteria are still relatively weak because the percentage of inhibition ability achieved is below 50%.